Aldosterone, mortality, cardiovascular events and reverse epidemiology in end stage renal disease. (6th September 2015) - Abd ElHafeez, Samar; Tripepi, Giovanni; Mallamaci, Francesca; Zoccali, Carmine
Abstract Background Plasma aldosterone is markedly increased in end stage renal disease (ESRD). The relationship between aldosterone, all‐cause and cardiovascular (CV) mortality in observational studies performed so far is controversial. Design We investigated the relationship between aldosterone, mortality and CV events in multivariate analyses including nutrition status, inflammation, LV function and fluids volume biomarkers in 278 ESRD patients without heart failure at baseline. Results In univariate analyses aldosterone was an inverse predictor of death (3rd tertile vs. 1st tertile Hazard ratios (HR): 0·58; 95% confidence interval (CI) 0·38–0·90. P = 0·01) and CV events (HR: 0·63; 95% CI 0·41–0·96; P = 0·03). Data adjustment for inflammation and malnutrition biomarkers substantially reduced the inverse relationship between aldosterone, mortality and CV events to be largely not significant (P = 0·31 and P = 0·36, respectively). The same was true by adjusting for volume expansion and LV dysfunction (left atrial volume and atrial natriuretic peptide) biomarkers (P = 0·30 for both outcomes). In a model adjusting for the full set of biomarkers of protein energy wasting/inflammation and volume expansion/LV dysfunction the inverse relationship between aldosterone and death and CV events was nullified (HR for death 0·98, P = 0·93; HR for CV events 0·96, P = 0·87). Conclusions Aldosterone is an inverse predictor of mortality and CV events in ESRD patients. This seemingly paradoxical relationship is abolished by statistical adjustment for inflammation, protein energy malnutrition, and volume expansion biomarkers indicating that it is the mere expression of the confounding effect of these factors. A clinical trial is needed to establish if aldosterone antagonism may improve clinical outcomes in ESRD.